An Introduction to Pennsylvania Legal Research for Academic Librarians and Researchers - Peter J Egler (Pennsylvania Libraries: Research & Practice, 2022)
This article reviews electronic Pennsylvania legal research resources available to academic librarians and researchers, the structure of the Pennsylvania state government, and the types of information published by each branch of the government. The executive branch publishes the Pennsylvania Bulletin (the state’s administrative register) and the Pennsylvania Code (the state’s administrative code). The laws passed by the Pennsylvania state legislature are codified in two separate statutory codes: Pennsylvania Consolidated Statutes and Pennsylvania Statutes. The legislature also publishes legislative history for statutes that can help to determine the intent of the legislature when the law was passed. The Pennsylvania courts consist of trial courts, two intermediate appellate courts, and a supreme court. All levels of courts publish case decisions and rules to govern court procedure. Citators help to determine whether a case decision is still valid.